The Role Of Organizational Commitment In Mediating Employee Engagement And Work Environment On Employee Performance - Maulida Nidaul Fadhliyah; Prihatin Tiyanto P.H; Gita Sugiyarti (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This research aims to analyze the influence of employee engagement and the work environment in the hotel environment both directly and indirectly through organizational commitment as an intervening variable. The population used was all hotel employees at three hotels in Central Java, namely Hotel Adhiwangsa Surakarta, Whiz Pemuda Semarang, and Hotel Grand Wahid Salatiga. The sample used was a saturated sample or census with a total of 147 respondents. The analysis techniques used are multiple linear regression analysis, path analysis and Sobel test. The results of this research found that (1) employee engagement has a positive and significant effect on employee performance (2) the work environment has a positive and significant effect on employee performance (3) employee engagement has a positive and significant effect on organizational commitment (4) the work environment has a positive and significant effect significant effect on organizational commitment (5) organizational commitment has a positive and significant effect on employee performance (6) organizational commitment is able to mediate but has a small effect on the relationship between the influence of Employee Engagement on employee performance (7) organizational commitment is able to mediate but has a small effect on the relationship the influence of the work environment on employee performance.